Geographic Information System (GIS) and Its Application in Urban Planning and Environment - Akbari, Masood Safari Ali (International Journal of Geography and Geology, 2014)
Using satellite data and GIS, the location of various urban land uses, including new methods for locating is quick. This study, based on a method of analysis - descriptive, and benefit from the resources in this area to assess the effectiveness of GIS in urban planning and environment, is discussed, and attempted to make a clear point of view, this can provide. Our results indicate that, nowadays, several researchers, from capabilities of GIS are used for localization. Because GIS is able to analyze large amounts of data layers is. Use of GIS in urban planning, with the rapid expansion of cities and increased levels of SAM binding information that must be processed for urban management, is clear. Abnormal location for the development of suitable sites for the establishment of urban green spaces, places for waste disposal and land evaluation, and its features and many other environmental issues, it can be pointed out.